Implementing Environmental Management Accounting: Status and Challenges - Rikhardsson, Pall M.; Bennett, Martin; Bouma, Jan Jaap; Schaltegger, Stefan (Eco-Efficiency in Industry and Science, 2005)
This is the third volume in the Environmental Management Accounting Network (EMAN) series of selected refereed papers on environmental management accounting drawn primarily from papers presented at EMAN-Europe's annual c- ferences. Most of the papers in this volume were ?rst presented at the 6th EMAN- Europe Annual Conference at the Aarhus School of Business, Denmark, on 23-24 January 2003. The focus of the conference and the papers presented was on implementation of Environmental Management Accounting. That is to say what challenges there are in getting EMAto work in companies, how governments are promoting EMAand how EMA can be supported by for instance IT. From the papers in this volume it can be seen that EMAis becoming more established as a ?eld of practice as well as an a- demic endeavour. EMA is no longer the sole interest of large multinational c- panies but is being adopted by SMEs as well as being promoted by various gove- ment agencies. EMAN has continued to play an important role in this development by providing a medium through which those interested can contact others with similar interests, and by organising regular events for the dissemination and exchange of news and ideas. EMAN aims to provide a forum in which academics and practitioners can meet to exchange and share ideas and experiences, and this has guided the selection of these papers which include both academic papers grounded in the relevant literature and with reference to theory as appropriate.